Seasonal Dry Matter Production and Nitrogen Fixation of Leucaena (Leucaena Leucocephala) and Stylo (Stylosanthes Guianensis) in Pure Swards and in Association with Signal Grass (Brachiaria Decumbens) - Abdullah, Aminah (1989)
An experiment was conducted to study the effects of rates of fertiliser nitrogen (N) and grass-legume associations on seasonal and annual dry matter production and forage quality factors of signal grass (Brachiaria decumbens). This study was also designed to es timate the amounts of N2 fixed over the first two years of establishment by pure stands of leucaena (Leucaena leucocephala cv. ML 1) and stylo (Stylosanthes guianensis cv. Schofield) or their mixtures with signal grass. Leucaena and s tylo were either grown in pure swards or mixed in various combinations wi th signal grass unfertilised with N. Dry matter production from legumebased pasture was compared with signal grass fertilised with urea at 0, 200, 400, 600 or 800 kg N ha-1yr-1.